Applied Biological Control in Brazil: From Laboratory Assays to Field Application. Issue 2 (7th March 2019) - Postali Parra, José Roberto; Coelho, Aloisio
Abstract: Brazil has a long history of the use of biological control (BC) of pests. The first attempt to use parasitoids was reported in the 1930s, and the first successful case dates to 1967. For a long period, chemical products were the most widespread control measure among Brazilian growers. This situation has gradually changed because of the lack of satisfactory control to manage certain pests, a slow change in the culture of growers, and some emblematic cases of the successful use of BC. The use of BC as a component of Integrated Pest Management is increasingly common. The present contribution summarizes the evolution of BC in Brazil, citing as an example the case of successful use of Cotesia flavipes (Cameron) (Hymenoptera: Braconidae), Tamarixia radiata (Waterston) (Hymenoptera: Eulophidae) and Trichogramma spp. It presents some data on the utilization of BC in the country, such as the case of sugarcane, for which microorganisms as well as macroorganisms are used; the use of Baculovirus in soybean, produced in mass-reared lepidopteran larvae; and the recent case of the control of Diaphorina citri Kuwayama (Hemiptera: Liviidae) by the parasitoid Tamarixia radiata . Finally, the prospects for wider use of BC in Brazil are discussed, together with the challenges involved in broadening the growers' use of this technology.